2019
DOI: 10.1038/s41523-019-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

The phosphatase PPM1A inhibits triple negative breast cancer growth by blocking cell cycle progression

Abstract: Estrogen receptor (ER)-negative, progesterone receptor (PR)-negative and HER2-negative, or “triple negative,” breast cancer (TNBC) is a poor prognosis clinical subtype that occurs more frequently in younger women and is commonly treated with toxic chemotherapy. Effective targeted therapy for TNBC is urgently needed. Our previous studies have identified several kinases critical for TNBC growth. Since phosphatases regulate the function of kinase signaling pathways, we sought to identify critical growth-regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…Kim et al found that Vanicoside B inhibited the expression of CDK8-mediated signaling pathways and epithelial transforming proteins, and it induced cell-cycle arrest in MDA-MB-231 and HCC38 cells [153]. The protein phosphatase, Mg 2+/ Mn 2+ -dependent 1A (PPM1A), a member of Ser/Thr protein phosphatase 2C family, is involved in regulating proliferation, cell invasion, and migration through reducing CDK and RB phosphorylation in TNBC [154]. Yu et al found that the inhibition of the subunit of the COP9 signalosome complex subunit 4 (CSN4) increases the sub-G1 cell population and induces apoptosis via regulating CDK6 in the BC cell line MDA-MB-231 [155].…”
Section: The Novel Cdk Inhibitors In Bcmentioning
confidence: 99%
“…Kim et al found that Vanicoside B inhibited the expression of CDK8-mediated signaling pathways and epithelial transforming proteins, and it induced cell-cycle arrest in MDA-MB-231 and HCC38 cells [153]. The protein phosphatase, Mg 2+/ Mn 2+ -dependent 1A (PPM1A), a member of Ser/Thr protein phosphatase 2C family, is involved in regulating proliferation, cell invasion, and migration through reducing CDK and RB phosphorylation in TNBC [154]. Yu et al found that the inhibition of the subunit of the COP9 signalosome complex subunit 4 (CSN4) increases the sub-G1 cell population and induces apoptosis via regulating CDK6 in the BC cell line MDA-MB-231 [155].…”
Section: The Novel Cdk Inhibitors In Bcmentioning
confidence: 99%
“…Consequently, some of the responding productions such as Snail, connective tissue growth factor and matrix metalloproteinases would be released and further result in EMT ( 25 ). PPM1A is a phosphatase of the serine/threonine PPM family and the main substrates of PPM1A include MAPK, Smad2 and Smad3 and MKKs ( 12 14 ). PPM1A serves an important role in the signal transduction of TGF-β/Smad signaling and can inactivate TGF-β/Smad signaling by dephosphorylating Smad2/3 ( 26 , 27 ) ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Protein phosphatase Mg 2+ /Mn 2+ -dependent 1A (PPM1A) serves an important role in the signal transduction of TGF-β/Smad signaling and can inactivate TGF-β/Smad signaling by dephosphorylating Smad2/3. PPM1A functions as a tumor suppressor in bladder and breast cancer via regulating cell invasion, EMT and cell cycle progression ( 12 14 ). As part of a continuing study on the molecular mechanisms of JMSD, the present study further examined the role of PPM1A in the anti-EMT activity of JMSD on AECs.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, ER status is usually assessed by immunohistochemical staining to assess protein expression. Currently, selective estrogen receptor modulators and aromatase inhibitors are used alone, or in combination with chemotherapy to treat ER-positive BRCA, which can significantly improve the survival rate of estrogen receptor-positive BRCA patients ( Mazumdar et al, 2019 ). However, the resistance to endocrine therapy drugs hinders the clinical treatment of ER-positive BRCA, and new endocrine therapy drugs need to be explored to overcome this challenge.…”
Section: Introductionmentioning
confidence: 99%